Hedge accounting within IAS39 - Alessandro Rossi; Guido Bichisao; Francesca Campolongo (European Investment Bank (EIB), 2002)
This work proposes an accounting calculation scheme for hedging swaps based on the requirements listed under International Accounting Statement (IAS) 39. In particular we developed a procedure that assists risk managers in the identification of the hedging efficiency between a group of loans (or bonds) and swaps held in a bank portfolio qualifying for hedge accounting. The proposed scheme aims at associating to any given swap of the bank portfolio, a certain collection of loans (or bonds) whose risk exposures offset each other. The final result is the construction of a number of hedges that are effective according to IAS 39.
Keywords: 330